The Effectiveness of Group Guidance with Experiential Learning Technique to Increase Students’ Creativity and Leadership - Dwi Sulistya Ningrum, Fatimatuz Zahra; Sugiharto, DYP; Awalya, Awalya (Jurnal Bimbingan Konseling, 2022)
Innovation and leadership skills are important competencies in the 21st century and can benefit counselors or guidance and counseling teachers. This study attempted to examine the effectiveness of a group guidance service with experiential learning technique to increase students’ creativity and leadership. This experimental study implemented control group pretest-posttest design and involved 20 students as the subjects divided into two groups. Creativity scale and leadership scales were employed to collect their data, these scales gained alpha coefficient of 0.98 and 0.83 respectively. Based on t-test results, the group guidance with experimental learning technique was effective to increase the creativity and leadership of the students of SMP Islam Nusantara in Plakat Tinggi Sub-district. Consequently, counselors are recommended to use experimental learning to increase the creativity and leadership of secondary school students in SMP or MTs.